EARLY DIALOGUE WITH HEALTH TECHNOLOGY ASSESSMENT BODIES: A EUROPEAN PERSPECTIVE. (30th March 2015) - Cuche, Matthieu; Beckerman, Rachel; Chowdhury, Cyrus A.; van Weelden, Marije A.
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction: Evidence requirements may differ across HTA bodies, and so pharmaceutical companies must plan to synergize their evidence generation strategy, across global regulatory and HTA bodies. Until recently, companies had no official platform to discuss the clinical development of a drug with HTA bodies; however, this is changing. Objectives: To achieve broad usage in the EU, products must achieve both regulatory and reimbursement approval, the latter of which is based on HTA appraisal in many markets. The objective of this study is to present and evaluate the different options available for early HTA consultation (during drug development/Phase III) in the major European markets from the industry perspective. Methods: An exploratory (nonsystematic) literature review was performed to identify the European markets offering early HTA consultations, and each process was analyzed using a set of predefined metrics that are relevant to industry (the ability to consult with the regulatory body in parallel, consultation fees, length of consultation meeting, language of consultation meeting, maximum number of pharmaceutical company employees attending, procedural timelines, nature of data for which consultative advice can be sought, the output of the process, and the ability to involve external experts). Results: Four different types of early HTA consultation processes were identified across the major European HTA markets. The nature of these processes varied in terms of the types and number of questions that can be addressed, the length of the meeting, the reporting output, and the ability to involve external experts. Conclusions: The availability of various options for early HTA consultation may help to avoid a mismatch between the evidence generated by means of a product's clinical development program, and the evidence expected by HTA bodies and payers, which can facilitate the pricing and reimbursement process upon a product's market authorization.